Contributions to Ziziphora clinopodioides (Lamiaceae) in Turkey and Iraq - Di̇rmenci̇, Tuncay; Haloob, Ali̇; Celep, Ferhat; Ghazanfar, Shahina A. (Phytotaxa, 2023)
While revising the genus Ziziphora for the Flora of Iraq and Turkey, we recognise seven subspecies for Z. clinopodioides. An identification key to these subspecific taxa is presented. A new subspecies, Z. clinopodioides subsp. brevistamina, is described and Ziziphora brantii is given a new subspecific status as Z. clinopodioides subsp. brantii. We have selected lectotypes for the subspecies brantii, kurdica, rigida and ronnigeri of Z. clinopodioides. Besides, Z. clinopodioides subsp. filicaulis is recorded for the first time for the Flora of Turkey.